Time‐lapse cameras reveal latitude and season influence breeding phenology durations in penguins - Black, C; Collen, B; Lunn, D; Filby, D; Winnard, S; Hart, T (Wiley, 2018)
Inter-specific variation in the phenology of avian taxa has long been studied to understand a species’ basic biology and how a species reacts to environmental changes over both space and time. Penguins (Sphenicidae) serve as an important example of how biotic and abiotic factors influence certain stages of seabird phenology because of their large ranges and the extreme conditions present in their Southern Ocean habitats. Here we examined the phenology of gentoo and chinstrap penguins to fill in gaps in our understanding of the dates within their annual cycles and to determine which phases are intrinsic, or rather vary across a species range and between years. We found that latitude and season had a predominant influence on the length of the nesting duration (first nesting activity to first egg laid), incubation duration (first egg laid to first chick hatched), and guard duration (first chick hatched to the last date both chicks seen guarded). The trend we observe here towards longer incubation times farther south, where ambient temperatures are colder, likely indicates that exposure to cold slows embryo growth within the egg. In addition, across species, in cases where loss or deaths occurred, colonies located farther south abandoned nests later and eggs or chicks were last seen in the nest at advanced dates in the breeding period. The variation in both space and time observed here in penguin phenology provides evidence that the duration of phases within the annual cycle of birds are not fundamental, or genetic, as previously understood. The recorded phenology dates should also inform field researchers on the best timing to count colonies at the peak of breeding and thereby control for count differences due to surveying the birds during different phenological phases.